IMPORT SUBSTITUTION AND MIGRATION POLICY - V. Y. Salamatov; S. I. Boldyrev; R. M. Gubenko (Стратегические решения и риск-менеджмент)
International migration has become an integral part of the globalization process and came to the fore on the agenda of world politics. During the given research a large amount of statistical material has been processed and visualized to assess capacity and  nature of labor markets in Russia and countries - members of the Shanghai Cooperation Organization. The basic trends, forming the key aspects of the State migration policy in this sector of economy, which are the factors of competitiveness and implementation of the program of import substitution are identified.